Praktik Endorsement oleh Influencer Tiktok Perspektif Akad Ijarah dan Fatwa MUI Nomor 24 Tahun 2017 tentang Hukum dan Pedoman Bermuamalah melalui Media Sosial - Suryaningtiyas, Adhiva Nurul Amalia (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
This research discusses endorsement practices by TikTok influencers and how to analyze the Ijarah contract and DSN MUI Fatwa Number 24 of 2017 on endorsements by influencers in the TikTok application. This research is qualitative research with a descriptive approach. The results of this study show that the endorsement system carried out by